On relaxed LMI-based design for fuzzy controllers - Teixeira, Marcelo C. M. [UNESP]; Assunção, Edvaldo [UNESP]; Avellar, Rodrigo G. [UNESP] (My University, 2001)
Relaxed conditions for stability of nonlinear continuous-time systems given by fuzzy models are presented. A theoretical analysis shows that the proposed method provides better or at least the same results of the methods presented in the literature. Digital simulations exemplify this fact. This result is also used for fuzzy regulators design. The nonlinear systems are represented by fuzzy models proposed by Takagi and Sugeno. The stability analysis and the design of controllers are described by LMIs (Linear Matrix Inequalities), that can be solved efficiently using convex programming techniques.
Keywords: Control of non-linear systems; Fuzzy control; Linear matrix inequalities (LMI); Quadratic stability; T-S fuzzy model